The specialty of Family Medicine for human resources training in Cuba - Lilia González Cárdenas (O Mundo da Saúde, 2010)
We discuss in this work the theme of Family Medicine as a very important specialty for human resources training in Cuba, from the Primary Attention to Health as a primordial teaching-caring and investigative setting. Cuban current society developed having a great deal of the above-mentioned problems already solved years ago. The process of medical education must correspond to social transformations, and this latter corresponds, by its turn, to medical practice, depending on the political will and health policies of each country. In our country, medical education happens in the community and for the community, emphasizing quality in health services; our force lies in Education in the work (study and work), a great effort in the promotion of health, the prevention of diseases, the education for health, teachers’ training and settings for teaching Family Medicine, residence programs of the specialty of Family Medicine happening in the community itself.